Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pengguna BPJS Pada Puskesmas Kandang Kota Lhokseumawe - Nurmalawati (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2024)
This research aims to determine the influence of service quality on patient satisfaction with BPJS users at the Kandang Community Health Center, Lhokseumawe City. The research method used is a quantitative research method with a simple linear regression equation model. In this research, the data source used is data from field research. The population in this study were BPJS patients at the Kandang Lhokseumawe City Health Center during the period 2024, totaling 9124 people with BPJS patient status who had visited the Kandang Lhokseumawe Health Center more than once. The sample of respondents in this study was 100. The results of this study concluded that Service Quality has a positive influence on Patient Satisfaction. The results of the hypothesis test show that the calculated t value is 9.361 > the t-table value which is 1.6605, with a significance figure of 0.000 < 0.05 (5%). Thus, rejecting H0 and accepting Ha, which means there is an influence of service quality on patient satisfaction. The resulting simple linear regression model is Y = 6.620 + 0.844 X + e. Analysis of the coefficient of determination in this research with a value of 0.472 (47.2%) for the service quality variable has an influence on Patient Satisfaction (Y) at the Kandang Community Health Center, Lhokseumawe City, while the remaining 100-47.2% = 52.8% is caused by other variables not examined in this study